2016
DOI: 10.3109/10903127.2015.1115929
|View full text |Cite
|
Sign up to set email alerts
|

Association between Prehospital CPR Quality and End-Tidal Carbon Dioxide Levels in Out-of-Hospital Cardiac Arrest

Abstract: When controlling for known CPR quality variables, increases in CC depth, CC rate and CCRV were each associated with a statistically significant but clinically modest increase in EtCO2. Given the small effect sizes, the clinical utility of using EtCO2 to guide CPR performance is unclear. Further research is needed to determine the practicality and impact of using real-time EtCO2 to guide CPR delivery in the prehospital environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…The association between log-transformed ETCO 2 and CPR variables was assessed through linear mixed effect models. The authors concluded that a 10 mm increase in compression depth was associated with a 4.0% increase in ETCO 2 (p < 0.0001); a 10 vpm increase in ventilation rate with a 17.4% decrease in ETCO 2 (p < 0.0001); and a 10 cpm increase in compression rate with a 1.7% increase in ETCO 2 (p = 0.02) [15].…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The association between log-transformed ETCO 2 and CPR variables was assessed through linear mixed effect models. The authors concluded that a 10 mm increase in compression depth was associated with a 4.0% increase in ETCO 2 (p < 0.0001); a 10 vpm increase in ventilation rate with a 17.4% decrease in ETCO 2 (p < 0.0001); and a 10 cpm increase in compression rate with a 1.7% increase in ETCO 2 (p = 0.02) [15].…”
Section: Discussionmentioning
confidence: 97%
“…Two recent studies have investigated these relationships [14,15]. Sheak et al conducted a multicenter cohort study of 583 in-hospital and out-of-hospital cardiac arrests.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations